Upaya Peningkatan Maharah Kalam dan Qira’ah Melalui Kegiatan HABIBA (Hari Bahasa Inggris Bahasa Arab) di Madrasah Tsanawiyah Negeri 3 Medan - Al Ghozi, Haidarul Gholib; Khalisa, Nayla; Nadiyyana, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Arabic has four language skills, namely listening skills (maharah istima'), speaking skills (maharah kalam), reading skills (maharah qiro'ah) and writing skills (maharah kitabah). These skills are related to each other in order to master Arabic optimally. This research was conducted with the aim of obtaining information regarding increasing maharah kalam and maharah qiro'ah through foreign language activities at the Madrasah Tsanawiyah Negeri 3 Medan. Researchers used a qualitative approach method as the main basis for research by collecting data from interviews, observations and documentation. Then the research results were analyzed using analytical techniques by presenting the data according to the results of the interviews conducted. Then from the data results it can be seen whether the foreign language activities are appropriate for students personally or whether these activities actually have a bad impact on the students.